(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2022)
The aim of the research is to: (1) The level of linguistic intelligence of the members of the research sample in the city of Daraa is known. (2) The correlation between linguistic intelligence and academic achievement in the Arabic language is known among the subjects of the research sample. (3) Detecting the differences between the mean scores of the research sample according to the variables of sex and grade. (4) Prediction of academic achievement through the linguistic intelligence of the members of the research sample. The research sample consisted of 367 students of basic education (second cycle) in the city of Daraa. The research reached the following results: (1) The level of linguistic intelligence of the members of the research sample was average. (2) There is a statistically significant correlation between linguistic intelligence and academic achievement in the Arabic language. (3) There is a statistically significant difference between the averages of students’ answers on the scale of linguistic intelligence according to the gender variable, and this difference is in favor of females. (4) There is a difference of statistical significance between the averages of the students ’response according to the variable of the grade level, and this difference is in favor of the higher grade in the two dimensions of the scale and in the total score. (5) You can predict academic achievement in the Arabic language through the two dimensions of linguistic intelligence (auditory perception, verbal expression) and the overall degree.